Risk management in Islamic financial institutions (literature review) - Muhammad Ihyak; Segaf Segaf; Eko Suprayitno (Institute of Computer Science (IOCS), 2023)
In carrying out its duties and functions as a financial services entity, Islamic financial institutions must implement risk management properly, also including legal risk management. This research was conducted with the aim of knowing the legal risk management that must be applied to Islamic financial institutions. The research method used in this study is a literature study of data collection techniques with literature studies obtained from various sources. The findings of this study are that in carrying out their functions, Islamic financial institutions must understand inherent risks, in this risk there are three main factors that must be considered, namely, litigation factors, engagement weakness factors and non-statutory factors. In addition to having to pay attention to these inherent risks, Islamic financial institutions are also required to carry out sharia compliance which is directly supervised by DPS which is under DSN's supervision. This literature study research is expected to provide knowledge and an overview for Islamic financial institutions, especially staff or employees who handle legal risks in Islamic financial institutions.